Penggunaan Metode Sosiodrama dan Pengaruhnya Terhadap Peningkatan Siswa dalam Kemahiran Berbicara - Farhan Faizan; Maman Dzuliman; Wahyudin Wahyudin (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2020)
The purpose of this researchÂ Â how much influence the use of Sosiodrama Methode to increase student Speaking Skills in learning Arabic in class VIII MTs AlWashliyah Cirebon. And One of the factors that influence the success or failure of learning is the teacher. Therefore, teachers must be clever in choosing the right methods so that the expected learning objectives can be achieved to the maximum. One alternative that is used is to apply Sociodrama method in Speaking learning. That picture media is one of the learning media that is directed to facilitate students in understanding learning. And Sociodrama method is an effective method, because this method able to provide understanding for students and make them even more enthusiastic in learning, especially in Speaking Skills learning. This research uses quantitative methods with the type of Quasi experimental methods. Data collection methods in this study are by observation, tests and Documentation, while data analysis in this study is to use,normality test, homogeneity test t test and hypothesis test. The results of this study are that students' Skill of learning Arabic Speaking without using Sociodrama method in the control class is with a minimum value of 68, a maximum of 80 with an average of 72.46. students' Skill of learning Arabic Speaking with using Sociodrama methodÂ in the Experiment class with a minimum value of 75, a maximum of 92 with an average of 82, 42. This means that there is an influence of the use of Sociodrama method to increase ability students in the Speaking Skills.